2020
DOI: 10.1108/jbim-10-2018-0294
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Interactive Network Branding for business relationship development: insights from emerging markets

Abstract: Purpose This paper aims to clarify the meaning of Interactive Network Branding (INB) and demonstrate its importance for business relationship development, within a cross-cultural context of emerging markets (EM). More specifically, it integrates the idea of INB through its three branding dimensions into the first three relationship development stages introduced in the seminal article by Ford (1980). By bringing INB into relationship development, and by considering its embeddedness in a cultural context, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Moreover, the paper corresponds to the findings from business relationship studies in the EM context that argue about the importance of personalized business contacts for overcoming uncertainties in fast-changing business markets (see, e.g., Salmi and Mattsson, 2015;Koporcic and Ivanova-Gongne, 2019). In addition, it has been demonstrated that recommendations and business connections can create a base for deeper interactions between partners, thus corresponding to the study conducted by Håkansson and Snehota (2006).…”
Section: Vitalsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, the paper corresponds to the findings from business relationship studies in the EM context that argue about the importance of personalized business contacts for overcoming uncertainties in fast-changing business markets (see, e.g., Salmi and Mattsson, 2015;Koporcic and Ivanova-Gongne, 2019). In addition, it has been demonstrated that recommendations and business connections can create a base for deeper interactions between partners, thus corresponding to the study conducted by Håkansson and Snehota (2006).…”
Section: Vitalsupporting
confidence: 63%
“…Therefore, they are implemented as part of networking. These findings suggest that the INB process is complex, non-linear, and Koporcic and Halinen, 2018;Koporcic andTörnroos, 2019a, 2019b;Koporcic and Ivanova-Gongne, 2019).…”
Section: Vitalmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have paid increasing attention to emerging economies, which are experiencing rapid changes in their legal, institutional and economic environments (Cannizzaro and Weiner, 2018; Gu et al , 2008; Johnson and Tellis, 2008; Ju et al , 2018; Walters and Saeed, 2003; Zhou and Poppo, 2010). Prior studies have explored various strategic issues in emerging market contexts, including the effect of branding on business relationship development (Koporcic and Ivanovagongne, 2020), the impact of different strategic orientations on firm performance (Jiang et al , 2019; Yao et al , 2019) and the importance of relationship networks for firms (Chung, 2019; Dadzie et al , 2017; Mandjak et al , 2019). A few recent studies have also addressed NPD in emerging economies (Fletcherchen et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SMEs use networking activities to overcome several challenges in the international market (Ellis, 2000;Johanson and Vahlne, 2009) and to explore new opportunities. These firms focus on secure network building (Koporcic and Ivanova-Gongne, 2020;Koporcic and Tornroos, 2019) to be successful in the international market (Masiello and Izzo, 2019;Srivastava et al, 2018). More specifically, despite being part of the EU, these firms still experience issues such as market failure (Estrin et al, 2006).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%